Optimal Monetary Policy Responses to the Financial Crisis in the Context of a Macroeconomic Agent-Based Model with Dynamic Expectations - Gottfried Haber (Verein für Socialpolitik, 2010)
Within the context of an agent-based macroeconomic model with dynamic bounded-rational expectations, the most important transmission links between the real sphere of the European economy and the US financial markets crises are simulated: (a) the devaluation of financial assets, (b) global interest rate changes, (c) the drop in US demand on the world markets, and (d) loss of confidence in banks, companies, and markets. Depending on the specification of the expectation formation process, optimal monetary policy reactions change significantly. We conclude, that expectations matter, even more for calculating optimal monetary policies that for simply simulating the model.
Keywords: E50; E62; E63; 330; Agent-based economics; Mulit-agent models; monetary policy; fiscal policy; expectation formation